Menopausal Symptoms among Breast Cancer Patients: A Potential Indicator of Favorable Prognosis - Chen, Yong (Public Library of Science, 2013)
Menopausal symptoms have been suggested to be an indicator of better prognosis among patients treated for breast cancer, because women who experience these symptoms usually have a lower level of estrogen. We tested this hypothesis in a population-based, prospective cohort study involving 4,842 women with stage 0 to III primary breast cancer who were enrolled in the Shanghai Breast Cancer Survival Study between March 2002 and April 2006, were aged 20 to 75 years, and were recruited 6 months post-diagnosis. They were followed-up by in-person surveys and record linkages with the vital statistics registry. Cox regression analysis was used to evaluate the association of menopausal symptoms at baseline with breast cancer recurrence. Approximately 56% of patients experienced at least one menopausal symptom, including hot flashes, night sweats, and/or vaginal dryness at baseline. During a median follow-up period of 5.3 years, 720 women had a recurrence. Experiencing hot flashes or having ≥2 menopausal symptoms was associated with lower risk of recurrence among premenopausal women (hazard ratio [HR]=0.77, 95% confidence interval [CI]: 0.62-0.96 for hot flashes; 0.73, 0.56-0.96 for ≥2 menopausal symptoms). Lower recurrence risk in relation to hot flashes was also observed among women who were not overweight/obese (HR=0.78, 95% CI: 0.64-0.99), those with relatively low waist-to-hip ratio (WHR) (HR=0.77, 95% CI: 0.61-0.97), and those who used tamoxifen (HR=0.75, 95% CI: 0.58-0.98). Consistently experiencing multiple menopausal symptoms was associated with lower recurrence risk among women with low WHR or who used tamoxifen. This large, population-based cohort study of women with breast cancer confirms that experiencing menopausal symptoms is an indicator of favorable breast cancer prognosis.